White rice-based carbohydrate diets as diet-induced obesity model in rats - Subramaniam, Jeevetha (2014)
High fat intake is a typical dietary pattern that is commonly consumed by Western populations. This diet is widely used in diet-induced obesity studies using animal models. On the other hand, in most Asian countries including Malaysia, dietary carbohydrate particularly white rice is a staple diet. Nevertheless, study on diet-induced obesity using white rice is limited. Therefore, this study aimed to investigate whether the Experimental Diet i.e. White Rice-based Carbohydrate Diets (WRBCD) can be used as a diet-induced obesity model in rats. It was hypothesized that, WRBCD were effective as a Corn-Based High Fat Diet (CBHFD) to induce obesity in rats. This study was divided into two phases; Phase I was a pre-experimental study and Phase II was an experimental study. In Phase I, nutrient and amylose content of selected white rice; namely fragrant white (FWR) and white rice, 5% broken (WR5%) were determined. White rice with lower amylose content was used at Phase II to prepare WRBCD. In Phase II, a total of 40 rats were divided equally into (i) Control group (Normal Purified Rat Diet (PD) and High Fat Diet (HFD)) and (ii) Experimental group (Normal (NCHORice) and High Carbohydrate Rice Diet (HCHORice)). A total of 8 rats died due to cardiac puncture procedure after the acclimatization period. Thus, there were only 32 rats included in the 8 weeks study. Obesity in rats was measured using body weight and body composition, while metabolic parameters including fasting plasma glucose, triglyceride and insulin levels were assessed. Rats were sacrificed at the end of study to measure weight of heart, kidney, liver, abdominal fat and thigh fat. In this study, the WR5% contained comparable amount of ash, fat, protein and available carbohydrate with the FWR (p>0.05). FWR had comparable amylose content with WR5% (p>0.05). Both WR5% and FWR were categorized as low amylose and therefore, WR5% or FWR rice can be used for Phase II. At Phase II, all the baseline parameters were comparable in all groups. After 8 weeks period, HFD (n=10) had comparable body weight (466.4 ±32.3 g) with NCHORice (n=7) (457.4 ±42.9 g) and HCHORice (n=7) (450.4 ±48.7 g) (p>0.05). In terms of body composition of the rats, rats consumed NCHORice (78.4 ±13.0 g) had the highest while rats in PD (59.3 ±4.4 g) had the lowest fat mass; the differences were significant (p<0.05). Total mass (378.0 ±16.4 g), lean body mass (308.6 ±12.7 g) and bone mineral content (8.6 ±0.5 g) were significantly highest in HFD (p<0.05) as compared to the other three groups. At the end of the study, weight of heart, kidney, liver and abdominal fat of the rats were comparable except for thigh fat. The thigh fat weight of the rats in HCHORice (6.8 ±2.2 g) was significantly higher than NCHORice (2.6 ±1.3 g) (p<0.05). For the metabolic parameters, all baseline data were comparable. The HCHORice group rats exhibited the highest fasting plasma glucose (16.9 ±2.4 mmol/L) and the highest fasting triglyceride (1.3 ±0.0 mmol/L) (p<0.05) than the other 3 groups at the end of the study. The insulin level of HFD (41.9 ±2.5 mU/L) was significantly higher than PD (33.9 ±1.5 mU/L) and NCHORice (36.3 ±1.1 mU/L) groups (p<0.05) after 8 weeks of the study. This study shows that WRBCD were effective as HFD to induce obesity in rats. Despite having comparable body weight in all groups, rats in WRBCD had produced highest blood glucose level (HCHORice) and highest fat mass (NCHORice) than the HFD. Thus, it can be concluded that WRBCD can be used as a diet-induced obesity model in rats.